2018
DOI: 10.1371/journal.pone.0199447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a unilateral hind limb orthotic lift on upper body movement symmetry in the trotting horse

Abstract: In trotting horses, movement asymmetry is associated with ground reaction force asymmetry. In humans, limb length differences influence contralateral force production. Here we investigate whether horses, in immediate reaction to limb length changes, show movement asymmetry adaptations consistent with reported force differences. Aim of this study was to quantify pelvic and compensatory head and withers movement asymmetry as a function of limb length changes after application of orthotic lifts. In this experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…However, some level of kinematic and kinetic asymmetries is often found in sound, well‐performing horses in both walk6,7 and trot8‐11 with considerable overlap being reported between low‐grade lameness and normal horses 12. Laterality, defined as a systematic preference to use one side of the body as a consequence of cerebral lateralisation,13 is discussed as one possible cause for locomotor asymmetries in healthy horses, but other possible factors are conformation,14 trimming and shoeing,15 training16 and pathological or age‐related changes. Vertical movement asymmetry increased only marginally in sound trotting horses after the addition of lead weights to the saddle and the rider,17 whereas horses became more asymmetrical with a professional rider vs a novice rider of similar bodyweight 18.…”
Section: Introductionmentioning
confidence: 99%
“…However, some level of kinematic and kinetic asymmetries is often found in sound, well‐performing horses in both walk6,7 and trot8‐11 with considerable overlap being reported between low‐grade lameness and normal horses 12. Laterality, defined as a systematic preference to use one side of the body as a consequence of cerebral lateralisation,13 is discussed as one possible cause for locomotor asymmetries in healthy horses, but other possible factors are conformation,14 trimming and shoeing,15 training16 and pathological or age‐related changes. Vertical movement asymmetry increased only marginally in sound trotting horses after the addition of lead weights to the saddle and the rider,17 whereas horses became more asymmetrical with a professional rider vs a novice rider of similar bodyweight 18.…”
Section: Introductionmentioning
confidence: 99%
“…The prominence of the road nail on the underside of the shoe effectively creates a very small lengthening of the limb with the nail compared to the contralateral limb. The effect of artificially lengthening one hindlimb -termed 'orthotic lift' -has been investigated previously using the same approach as used here: upper body movement symmetry based on IMU measurements [28]. Interestingly, midline pelvic (sacrum) movement asymmetry was shown to be affected by lengthening, while tuber coxae movement asymmetry (HHD) was not [28].…”
Section: Discussionmentioning
confidence: 93%
“…The effect of artificially lengthening one hindlimb -termed 'orthotic lift' -has been investigated previously using the same approach as used here: upper body movement symmetry based on IMU measurements [28]. Interestingly, midline pelvic (sacrum) movement asymmetry was shown to be affected by lengthening, while tuber coxae movement asymmetry (HHD) was not [28]. This is opposite to the findings of the present study, where HHD was affected by the presence of a road nail but midline pelvic movement asymmetry parameters (PDmin, PDmax, PDup) were not.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that hindlimb length asymmetry does not create the same artefactual effect (a measured lameness caused only by limb length asymmetry) on measures of hindlimb lameness associated with pelvic rotation (hip hike, hip dip). Hip hike was not affected when elevation was placed on one hindlimb and horses were evaluated trotting in a straight line (8).…”
Section: Limitationsmentioning
confidence: 99%
“…The effect of hindlimb length difference induced by hoof height elevation on equine hindlimb lameness has been initially studied by Vertz, et al in 2018, where it was found that minimum and maximum pelvic height differences, as measures of hindlimb lameness, were significantly influenced in horses trotting in a straight line. However, in this study the effect of hindlimb length difference was only evaluated in horses trotting in a straight line on hard surfaces, limited conditions compared to common clinical evaluation [8].…”
Section: Introductionmentioning
confidence: 99%